Analytical Quality by Design (AQbD)-oriented RP-UFLC method for quantification of lansoprazole with superior method robustness. Issue 9 (28th May 2017) - Panda, Sagar Suman; Ravi Kumar Bera, Venkata Varaha; Beg, Sarwar; Mandal, Omkar
ABSTRACT: A reversed-phase ultrafast liquid chromatography method was developed for quantification of lansoprazole in pharmaceutical dosage form using analytical quality by design approach. Systematic planning and experimentation using design of experiment approach were used for method development and optimization studies. A central composite design was used for optimizing the chromatography, by choosing organic phase proportion and flow rate as the critical method variables for evaluating their effect on critical analytical attributes like resolution, plate number, and tailing factor. The optimal chromatography was accomplished on a C-18 column (250 × 4.6 mm, 5 µm) using methanol:water (70:30, v/v) as mobile phase at a flow rate of 1.0 mL/min. Photo diode array (PDA) detection was performed at 284 nm. Caffeine was used as the internal standard. Method validation studies revealed that the calibration curve was linear over 1.0–300 µg/mL. The method was found accurate with average recovery between 98.99 and 102.87%. The percent relative standard deviation values obtained for precision were as per ICH guideline and within the acceptance limits (<2%). Results of system suitability indicated superior method robustness. In a nutshell, the method was found to be highly suitable for its applicability in the determination of lansoprazole in bulk and tablet dosage form. GRAPHICAL ABSTRACT: